Antibacterial Activity of Staphylococcus capitis, Bacillus cereus, Pantoea dispersa From Telang Flower (Clitoria ternatea L) Kombucha Bath Soap as a Pharmaceutical Biotechnology Product - Kolo, Yuliana; Rezaldi, Firman; Fadillah, M. Fariz; Ma'ruf, Aris; Pertiwi, Fernanda Desmak; Hidayanto, Fajar (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2022)
Telang lower kombucha is a probiotic drink that has the potential to enhance the immune system, active cosmetic ingredients, and its waste has been proven to be used as an organic liquid fertilizer preparation. The purpose of this study was to make a formulation and preparation of liquid bath soap with an active ingredient in a solution of seagrass kombucha fermentation at a sugar concentration of 20%, 30%, and 40% in inhibiting the growth of S. capitis, B. cereus, and P. dispersa bacteria. via the disc diffusion method. The results of the study have proven that based on the post hoc test analysis, kombucha bath soap at a concentration of 40% is significantly different from the concentration of 20% and 30% but not significantly different from the positive control and the concentration of 40% is the best concentration in inhibiting the growth of the three test bacteria. compared with the treatment and the two comparisons.